Elastic and structural properties of sputtered refractory metal thin films - Yakupov, T.; Utegulov, Z. N.; Demirkan, T.; Karabacak, T. (Nazarbayev University, 2014)
To fabricate optimal hard and wear-resistant coatings it is necessary to tailor their mechanical and structural properties for an optimal industrial application. We are exploring elastic and structural properties of refractory metal (Ta, Nb, Mo and W) thin films of different thicknesses fabricated by DC magnetron spattering technique on single crystalline Si substrates.
Keywords: elastic; structural properties; metal